The Effect of Waterpipe Tobacco Smoking on Bone Healing Following Femoral Fractures in Male Rats - Sadeghifar, Amirreza; Sheibani, Mohamad; Joukar, Siyavash; Dabiri, Shahriar; Alavi, Samanehsadat; Azari, Omid; Vosoghi, Darioush; Zeynali, Yas; Zeynali, Yasman; Shahraki, Mohamad; Torghabe, Amirhesam; Rostamzadeh, Farzaneh; et al. (Frontiers in Surgery, 2021)
Background: Given the increasing use of waterpipe tobacco smoking in the world and its unknown effects on bone healing, this study investigated the repairing of femoral bone fractures in rats exposed to waterpipe tobacco smoking (WTS). Main Methods: This study involved 40 male Wistar rats that were divided into two groups, including the femoral fracture (Fx) and the Fx + WTS groups. Each group was divided into two subgroups that were evaluated for bone healing 28 and 42 days after femoral fracture. After fixing the fractured femur, the healing process was evaluated by radiography, pathological indicators, and a measurement of the blood levels of vascular endothelial growth factor (VEGF), parathyroid hormone (PTH), Ca ++, transforming growth factor-beta (TGF-β), and insulin-like growth factor 1 (IGF-1). Additionally, the density of VEGF and CD34 in fracture tissue was investigated by immunohistochemistry. Key Findings: Radiographic findings showed that factors related to the earlier stages of bone healing had higher scores in the Fx + WTS28 and 42 subgroups in comparison to the Fx groups. The density of VEGF and CD34 showed that the angiogenesis processes were different in the bone fracture area and callus tissue in the Fx +WTS subgroups. The serum levels of VEGF, TGF-β, and IGF-1 were significantly lower in the Fx +WTS42 group, and PTH in the Fx +WTS28 group was higher than that in the other groups. Significance: The findings showed the disturbance and delay in the femoral fracture union in rats exposed to hookah smoke. This is partly due to the reduction of molecular stimuli of bone synthesis and the attenuation of quantitative angiogenesis.